The West Wing. The complete fifth season [videorecording (DVD)] - Sheen, Martin; Channing, Stockard; Hill, Dulé; Janney, Allison (Warner Home Video, 2005)
Follow the drama when the government is temporarily passed from a Democratic administration to the Republican Speaker of the House, as President Bartlet copes with the kidnapping of his youngest daughter Zoey.